Aerobic and anaerobic capacities, flexibility and muscular performance of young female sedentary individuals, silat and taekwondo practitioners - Anowar, Muhamad Nazri Mohd (Universiti Sains Malaysia, 2017)
This study investigated physical fitness components of aerobic and anaerobic capacities, flexibility and muscular performance of young female sedentary individuals, silat and taekwondo practitioners. Thirty six young female participants with age ranged 15 to 20 years old were recruited. There were three groups with 12 participants per group in this study. The groups were sedentary control group, silat group and taekwondo group. All participants performed anthropometric and body composition assessments, aerobic capacity measurement via estimated maximum oxygen uptake (VO2max) test, Wingate test anaerobic capacities test, flexibility measurement via sit and reach test, muscular strength and explosive power measurements via hand grip strength test, back and leg strength test and standing long jump explosive power test. One-Way ANOVA was performed to determine the differences of the measured parameters among groups. This study found that silat group showed significantly (p<0.05) greater flexibility and handgrip strength of dominant and non-dominant hands compared to sedentary control group. Taekwondo group showed greater value of estimated VO2max compared to sedentary control group and silat group respectively. There were no significant differences in back and leg strength, jumping explosive power and Wingate anaerobic capacities among sedentary control, silat and taekwondo groups. In conclusion, these findings imply that engagement in silat and taekwondo could enhance certain physical fitness components compared to sedentary lifestyle. Silat practitioners are characterised by high flexibility and strong hand muscle. Both taekwondo and silat practitioners possessed similar anaerobic capacity, however, taekwondo practitioners showed higher aerobic capacity than silat practitioners. It is hoped that the present findings obtained from this study can be used as guidelines for planning training programs for taekwondo and silat practitioners, as well as promoting active lifestyle by engaging in martial arts such as taekwondo and silat.